Music Of The Tabom: Its Cultural Background And Style - Amakye-Boateng, B. (University of Ghana, 2017)
Negotiating identity is a key factor to a people surrounded by many other differences such as other ethnic groups and communities with different orientations. Such is the story of the Tabom who are African slave returnees from Brazil. The music or organised sound related to their existence helps in the creating of their unique identity as it relates to being Ga on one side, and having had contact with the outside world on the other. Agbe, the music of the Tabom is one of the avenues by which the story, culture, and identity of the Tabom can be studied. To date, all anthropological studies done on the Tabom (Boadi-Siaw 1993, Amos and Ayensu 2002 Schamloeffel 2008, Essien 2010, and Von Hesse 2014) only mention in passing the music-Agbe as a mere practice but not as a normative functional element to the creation of the Tabom identity. This dissertation argues from an ethnomusicological perspective that Agbe as an organised sound in relation to the life and culture of the Tabom serves the purpose of creating and negotiating identity as found in their use of music as part of religious rites and as part of other important ceremonies such as in relation to the rites associated with the human life cycle. The dissertation sets forth the historical and social background of the Tabom, reveals the music and analyses every musical element and or device that the creators and the performers of the music utilise in bringing to the fore the priorities of the Tabom culture. A special interest of this dissertation is the study of rhythm, text, melody and the combination of any of these as well as other aids to musical performance in expressing the inner self that subsequently helps in shaping the Tabom identity. An in-depth analysis of the music using both western and African analytical tools such as the identification of scales, modes, and interval cycles/cyclic pitch collections as well as the African minimalist impulse and its relation to the other forms of art within the African culture.
Thesis (PhD)
Keywords: Tabom; Cultural Background; Style; Music